2014
DOI: 10.14311/ap.2014.54.0398
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Magnetic Fields and the Role of Frame Dragging Near Rotating Black Hole

Abstract: Magnetic null points can develop near the ergosphere boundary of a rotating black hole by the combined effects of strong gravitational field and the frame-dragging mechanism. The induced electric component does not vanish an efficient process of particle acceleration can occur. Furthermore, the effect of imposed (weak) magnetic field can trigger an onset of chaos. The model set-up appears to be relevant for low-accretion-rate nuclei of some galaxies which exhibit episodic accretion events (such as the Milky Wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…Previously, we have demonstrated that the structure of the electromagnetic field is strongly influenced by the relativistic effects of a spinning compact object (Karas & Kopáček 2009;Karas et al 2014Karas et al , 2012. In particular, we have shown that close to the event horizon, where the frame dragging dominates, these effects shape the field lines (described by the vacuum solution of Maxwell's equations) in a way that may mimic the behavior typically associated with magnetohydrodynamic plasma.…”
Section: Introductionmentioning
confidence: 76%
“…Previously, we have demonstrated that the structure of the electromagnetic field is strongly influenced by the relativistic effects of a spinning compact object (Karas & Kopáček 2009;Karas et al 2014Karas et al , 2012. In particular, we have shown that close to the event horizon, where the frame dragging dominates, these effects shape the field lines (described by the vacuum solution of Maxwell's equations) in a way that may mimic the behavior typically associated with magnetohydrodynamic plasma.…”
Section: Introductionmentioning
confidence: 76%
“…The combined effects of nonaxisymmetry and rotation on the structure of vacuum electromagnetic fields near compact objects has already been investigated by many authors; for the analyses especially close to our context, see Kopáček et al (2018) and Karas et al (2013Karas et al ( , 2014. As a consequence of profound changes in the topology of the field induced by breaking the axial symmetry, the dynamics of charged particles also changes dramatically and generally becomes more prone to deterministic chaos.…”
Section: Introductionmentioning
confidence: 86%
“…We have numerically located the NPs for different values of χ and discussed their location as a function of coordinate time t and radius of the conductor R. We conclude that NPs only form for some period of coordinate time t and that they are always located outside the conducting region of a magnetic star. Previously, we have also studied the formation of magnetic NPs in the curved spacetime of a rotating Kerr black hole [2,3,23]. Namely, we investigated the nearhorizon structure of an asymptotically uniform magnetic field (aligned or inclined with respect to the axis of rotation).…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%